Teachers of Russian Language and Literature in State Secondary Schools for Boys in the Kingdom of Poland in 1833-1862. The Number of Teachers, Career and their Assessment by Educational Board - Massalski, Adam (Respectus Philologicus, 2004)
After the fall of the November Uprising, Russian authorities began the Russification of the youth attending secondary schools. An important role was prescribed to Russian teachers who came from the Russian Empire. In the discussed period one hundred and forty-three teachers arrived in the Kingdom of Poland from Russia. They were mainly university graduates. The Education Board of the Kingdom of Poland had a lot of reservation towards their teaching methods and conduct in the environment. Therefore, the results of their thirty-year work aiming at Russification appear to have been insignificant. Additionally, the lack of success seems to have been conditioned by the fact that the Polish young generation did not pay much attention to learning Russian, which might have lowered the teachers' motivation to increased teaching efforts.
Keywords: education in the Kingdom of Poland in the first half of the nineteenth century; educational policy of the Tsardom; Russian teachers; career paths; teachers' job assessment